Comparison of phytochemicals and antioxidant properties of different fruit parts of selected artocarpus species from Sabah, Malaysia - Abu Bakar, Mohd Fadzelly; Abdul Karim, Fifilyana; Perisamy, Eeswari (Penerbit Universiti Kebangsaan Malaya, 2015)
The purpose of this study is to investigate and compare the phytochemical contents and antioxidant activity of 80% methanol extracts of three selected fruits of Artocarpus species namely, Artocarpus odoratissimus (tarap), Artocarpus kemando (pudu) and Artocarpus integer (cempedak). The total phenolic, total flavonoid and total carotenoid contents of different parts of the fruits (peel, flesh and seed) were analyzed spectrophotometrically. The antioxidant properties were assessed by DPPH, FRAP and ABTS method. The total phenolic content of all parts of the fruits ranging from 3.53 to 42.38 mg GAE/g of dry sample. The total flavonoid was in the range of 0.82 to 36.78 mg CE/g of dry sample whereas the total carotenoid ranging from 0.67 to 3.30 mg ß-carotene/g of dry sample. The peel and seed displayed higher phytochemical contents (as compared with the flesh) and were found to be efficient radical scavengers and reducing agents. Total phenolic and total flavonoid contents were significantly correlated with the antioxidant activities. However, the total carotenoid was weakly correlated with the antioxidant activities. Due to the findings of this research, it is observed that the phytochemical compounds are the major contributor to the antioxidant activities. A. odoratissimus has the potential to be used as antioxidant agents due to high phytochemical contents and high antioxidant activity for all tested methods.